2016
DOI: 10.1007/s10856-016-5708-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and physiological effect of tapioca maltodextrin colloid plasma expander in hemorrhagic shock and resuscitation model

Abstract: Plasma expanders (PEs) are administered fluids to replace blood volume when massive blood loss has occured. Maltodextrin from tapioca starch was selected as a study candidate to prepare a colloid PE due to an uncomplicated production process. The formulations of mixture between tapioca maltodextrin and 0.9 % sodium chloride solution were prepared and then characterized. This was to investigate the effects of a dextrose equivalent (DE) and the concentration on the physical properties. Storage stability of each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…The viscosities of HPS‐based PEs stored for 4 weeks were quite similar to Day 1 when stored either at 25 ± 2 °C or at 4 ± 2 °C. This viscosity stability is possibly due to the low retrogradation of hydroxypropyl, acid thinned tapioca starch, which is different from the results of PEs prepared from native tapioca starch and low DE tapioca maltodextrin …”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…The viscosities of HPS‐based PEs stored for 4 weeks were quite similar to Day 1 when stored either at 25 ± 2 °C or at 4 ± 2 °C. This viscosity stability is possibly due to the low retrogradation of hydroxypropyl, acid thinned tapioca starch, which is different from the results of PEs prepared from native tapioca starch and low DE tapioca maltodextrin …”
Section: Resultssupporting
confidence: 91%
“…Additionally, an increasing concentration of HPS increased COP in a nonlinear fashion as an exponential function. In our previous study, we found that tapioca maltodextrin colloid PE had a linear relationship to the concentration . Therefore, the type of starch derivative influences COP of PE.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations